2014
DOI: 10.3389/fncel.2014.00084
|View full text |Cite
|
Sign up to set email alerts
|

A major role for Tau in neuronal DNA and RNA protection in vivo under physiological and hyperthermic conditions

Abstract: Nucleic acid protection is a substantial challenge for neurons, which are continuously exposed to oxidative stress in the brain. Neurons require powerful mechanisms to protect DNA and RNA integrity and ensure their functionality and longevity. Beside its well known role in microtubule dynamics, we recently discovered that Tau is also a key nuclear player in the protection of neuronal genomic DNA integrity under reactive oxygen species (ROS)-inducing heat stress (HS) conditions in primary neuronal cultures. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
197
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(214 citation statements)
references
References 30 publications
3
197
0
1
Order By: Relevance
“…In neuronal or non-neuronal cells, nuclear Tau has been widely detected using pan-Tau antibodies. Further studies using various antibodies directed against phospho-dependent Tau epitopes confirmed the predominantly hypophosphorylated form of Tau in cell nuclei (20,24,27,29,52). Using the Tau1 antibody directed against a non-phosphorylated epitope of Tau protein (serine 195-202), differences in the sub-nuclear localization of Tau have been observed between human and murine cells.…”
Section: Possible Sources Of Nuclear Aicd A␤ and Taumentioning
confidence: 87%
See 2 more Smart Citations
“…In neuronal or non-neuronal cells, nuclear Tau has been widely detected using pan-Tau antibodies. Further studies using various antibodies directed against phospho-dependent Tau epitopes confirmed the predominantly hypophosphorylated form of Tau in cell nuclei (20,24,27,29,52). Using the Tau1 antibody directed against a non-phosphorylated epitope of Tau protein (serine 195-202), differences in the sub-nuclear localization of Tau have been observed between human and murine cells.…”
Section: Possible Sources Of Nuclear Aicd A␤ and Taumentioning
confidence: 87%
“…Going a step further, in primary neuronal cultures, endogenous hypophosphorylated nuclear Tau was shown to protect DNA integrity under oxidative and hyperthermic stress conditions (27). The DNA protective function of Tau has been validated in vivo in adult neurons in the brain of mouse submitted to hyperthermic stress and under physiological condition (29). Although Tau may protect DNA integrity through AT-rich minor groove binding (27), it does not preclude the involvement of Tau in the DNA damage response (29).…”
Section: Possible Nuclear Functions Of Aicd A␤ and Taumentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that a diffuse TUNEL-positive staining of the cytoplasm was only present after heating in AMF-treated tumors, reflecting an additional labeling of remarkably fragmented RNA (likely by the applied heat) due to the labeling of 3′-OH termini after the breakage of nucleic acids. 38 The sole AMF treatment has no impact on therapy outcome as it does not result in the unspecific heating of tissue, in particular, because much lower magnetic field amplitudes and frequencies are used compared to MRI. By reaching temperatures up to 50°C during the performed in vivo experiments, the observed remarkable tumor destruction in both heat-based treatments was hypothesized to be connected to the regulation and/or destruction of key proteins involved in apoptosis, cell survival, angiogenesis, and cell cycle.…”
mentioning
confidence: 99%
“…The precision of tau role in DNA protection and RNA integrity under physiological conditions or under ROSproducing stress (Violet et al, 2014) provides clarification for a mechanistic model in which tau disturbance initiates an explanation for DNA damages observed in AD. Principally, tau is a phosphoprotein.…”
mentioning
confidence: 99%